Chorea-like symptoms and high blood concentration of ceftriaxone in a patient undergoing hemodialysis: A case report. Issue 3 (March 2020) - Yokoyama, Yoshiaki; Hosokawa, Naoto; Kudo, Toshiyuki; Goda, Hitomi; Ito, Kiyomi; Suzuki, Masanori; Funakoshi, Ryohkan
Abstract: Ceftriaxone (CTRX) is a third-generation cephalosporin commonly used to treat infections such as community-acquired pneumonia and urinary tract infections caused by mainly Gram-negative bacteria and some Gram-positive bacteria. Here, we report a case of a patient on hemodialysis who had chorea-like symptoms with high blood concentration of CTRX. A 74-year-old Japanese woman receiving hemodialysis was admitted with obstructive cholangitis and was started on CTRX therapy at a dose of 2 g every 24 hours. On the 6th day after starting administration of CTRX, chorea-like symptoms appeared. We suspected that her symptoms were caused by a high blood concentration of CTRX. We performed a series of blood sampling to determine the concentration of CTRX at different time points before and after discontinuing CTRX administration. CTRX concentrations were higher than those expected in healthy adults, and her chorea-like symptoms had disappeared from the second day of discontinuation of CTRX. The association between CTRX blood concentration and chorea-like symptoms is unclear. However, measuring a series of plasma or serum concentrations from symptom onset to disappearance suggested that chorea-like symptoms appeared when the concentration exceeded approximately 450 μg/mL. Care should be taken when administering CTRX to patients with cholestasis undergoing hemodialysis, as blood CTRX levels may rise unexpectedly and result in complications.